ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PEMANEN KELAPA SAWIT DI PT SUMATERA SAWIT LESTARI (SSL) DI KABUPATEN MUSI RAWAS UTARA - Aldi, Jeck; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2025)
ABSTRACTThis study aims to analyze the factors that affect the productivity of harvest labor at PT SSL, focusing on working conditions, task distribution, worker health, and incentive policies. The research results are expected to provide recommendations to improve labor efficiency and welfare, so that the company's productivity can remain optimal. This study also aims to describe the characteristics of harvest labor and the factors that influence the productivity of oil palm harvesters at PT. Sumatera Sawit Lestari (SSL). The research method used in this study is the simple random sampling method. The informants in this study are 30 people who are oil palm harvest workers at PT. Sumatera Sawit Lestari (SSL). The data collection methods used in this study are observation, interviews, and documentation. The data processing methods used include editing, coding, and tabulating. Data were analyzed using a qualitative approach. The research results show that: (1) The characteristics of respondents include productive age over 40 years, covering 60.00% of the total respondents, with a work period of more than 11 years (83.34%), reflecting a high level of experience. The majority of workers have 3–5 family dependents and most travel a distance of 3–4 km to the plantation site. (2) Factors such as age, length of service, family dependents, and travel distance simultaneously have a significant effect on labor productivity, with an F-count value of 12.24 > F-table value of 2.69 at a 90% confidence level. However, partially, only length of service has a significant effect on labor productivity, with a t-count value of 15.888 > t-table 2.060 and p < 0.05. Other variables, namely age, family dependents, and travel distance, have t-count values < t-table and p > 0.05, so they do not have a significant effect. The R² value of 0.6620 indicates that the independent variables can only explain 66.20% of the variation in labor productivity, while the rest is influenced by other factors outside the model.  ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan karakteristik tenaga kerja pemanen dan faktor –faktor apa saja yang berpengaruh terhadap produktivitas tenaga kerja pemanen kelapa sawit di PT. Sumatera Sawit Lestari (SSL). Metode penelitian yang digunakan dalam penelitian ini adalah metode Simple random sampling. Informan dalam penelitian ini yaitu 30 orang yang merupakan para tenaga kerja pemanen kelapa sawit PT. Sumatera Sawit Lestari (SSL). Metode pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Metode pengolahan data yang digunakan (editing, coding dan tabulating). Menganalisis Data dengan menggunakan pendekatan Kualitatif. Hasil penelitian menunjukkan 1) Karakteristik responden meliputi usia yang dimana memiliki usia produktif >40 yang mencakup 60,00% dari total responden dengan masa kerja lebih dari 11 tahun (83,34%), mencerminkan tingkat pengalaman tinggi. Mayoritas tenaga kerja memiliki 3–5 tanggungan keluarga serta sebagian besar tenaga kerja menempuh jarak 3–4 km ke lokasi kebun. 2)  Faktor-faktor seperti umur, masa kerja, tanggungan keluarga, dan jarak tempuh secara simultan memiliki pengaruh signifikan terhadap produktivitas tenaga kerja, dengan nilai Fhitung sebesar 12,24  >  Ftabel sebesar 2,69 pada tingkat kepercayaan 90%. Namun, secara parsial, hanya masa kerja yang memiliki pengaruh signifikan terhadap produktivitas tenaga kerja dengan nilai thitung sebesar 15,888 > ttabel 2,060 dan p < 0,05. Variabel lainnya, yaitu umur, tanggungan keluarga, dan jarak tempuh, memiliki nilai thitung < ttabel dan p > 0,05, sehingga tidak memiliki pengaruh signifikan. Nilai R² sebesar 0,6620 menunjukkan bahwa variabel independen hanya mampu menjelaskan 66,20% dari variasi produktivitas tenaga kerja, sementara sisanya dipengaruhi oleh faktor lain di luar model.